Dinuclear zinc(II) dithiocarbamate macrocycles: ditopic receptors for a variety of guest molecules. - Wong, W; Curiel, D; Cowley, A; Beer, P (2005)
The synthesis of a series of dinuclear zinc(II) dithiocarbamate (dtc) macrocyclic receptors containing aryl spacer groups of different sizes is reported. As evidenced from 1H NMR titration investigations, these receptors have the ability to bind various neutral and anionic bidentate guests species, including 1,4-diazabicyclo[2.2.2]octane (DABCO), isonicotinate and terephthalate in a cooperative 1 : 1 intramolecular inclusion complex. Stability constant determinations reveal a correlation between the strength of complexation and complementary receptor cavity : guest molecule size. In particular, the X-ray structure of a 1 : 1 host-guest complex between a dinuclear zinc(II) dtc receptor and DABCO illustrates the cooperative nature in which the dinuclear receptor associates with the bidentate guest.